Pengaruh Media Video Siklus Hidup Hewan Terhadap Hasil Belajar Siswa Kelas IV SDN Mugarsari - Sovia Elsani; Akhmad Nugraha; Yusuf Suryana (Universitas Pendidikan Indonesia Kampus Serang, 2019)
Video media can help students in effectively understanding to abstract concepts. Many students did not perform their work and difficult to understand the abstract concept of the animals’ life cycle. The lack of understanding was caused by the lack interactive and conventional material delivery by the teacher. Teacher tried to improve students’ learning outcomes by developing strategies in learning science through videos. Therefore, this study aimed to describe the use of video media on the animals’ life cycle material on fourth grade learning outcomes. This quantitative research used quasi experimental design with pre-test and post-test by using a written test as instrument. The subjects of this study were students of class A and B of fourth grade of Mugarsari Elementary School. Based on the findings, the implementations of learning through videos positively enhance learning outcomes. By well-designed research plan and implementation of activities through learning videos, the students’ learning outcomes of experimental class improved. The the average score of experimental class learning outcomes by using video media is higher than the control class without using video media. Based on testing the hypothesis using the SPSS program version 20.0, t obtained 2.127 was higher than table of 2.034 with a significant level (α = 0.05). It concluded that there is a significant different on students’ understanding before and after learning by using video